Innovative applications of digital solutions and tools in educating IT school students - Gryniewicz-Jaworska, Michalina (Journal of Computer Sciences Institute, 2019)
Currently, digital skills have become an important factor for the development and active participation in today’s information society. The article describes innovative IT methods and tools used in the education process. New technologies and new methods of conducting classes form the basis of today’s education. Traditional methods have been replaced by digital tools that are perfect at the stage of educating school pupils in IT profiles, preparing them for vocational exams.